PELATIHAN PEMBUATAN SABUN BERBAHAN BAKU JELANTAH BAGI IBU PKK DI NAGORI DOLOK MARAJA KABUPATEN SIMALUNGUN - Rudi Salman; Herlinawati; Irfandi; Dewi Endriani (Bahasa Indonesia, 2020)
Abstract Scientifically soap is a mixture of sodium or potassium salts from fatty acids which can be derived from oil or fat which is reacted with lye (sodium or potassium hydroxide) through a saponification process. One of the raw materials for making soap is fat found in cooking oil waste (used for cooking). Dolok Maraja village has great potential in this soap-making business with the number of heads of families (KK) reaching 1449. Each month it produces 1 kg of cooking per family. So in 1 month about 1449 kg of used cooking is produced. The aim of the training on making used used soap is to develop the potential of the women of the Dolok Maraja Village PKK in creating soap products made from used cooking raw materials, which are household needs. The presenters and instructors from the Physics and Chemistry Education Study Program lecturers came to Dolok Maraja Village, then provided information and training to PKK women about making soap made from used cooking ingredients. Based on the results of the average score scores from the evaluation and mentoring carried out by the PKM Unimed team, the process of making solid soap which was followed by 10 participants was able to master immaterial in the Very Good category. For the manufacture of liquid soap with 16 participants in the Good category. Meanwhile, making dab soap is included in the category of not mastering because the process is quite long. Abstrak Secara ilmiah sabun merupakan campuran garam natrium atau kalium dari asam lemak yang dapat diturunkan dari minyak atau lemak yang direaksikan dengan alkali (natrium atau kalium hidroksida) melalui suatu proses saponifikasi. Salah satu bahan baku pembuat sabun adalah lemak yang terdapat pada limbah minyak goreng (jelantah). Desa Dolok Maraja sangat berpotensi dalam usaha pembuatan sabun ini dengan jumlah Kepala Keluarga (KK) mencapai 1449. Setiap bulannya menghasilkan jelantah 1 Kg/keluarga. Maka dalam 1 bulannya dihasilkan sekitar 1449 kg jelantah. Tujuan pelatihan pembuatan sabun berbahan baku jelantah ini adalah untuk mengembangkan potensi ibu-ibu PKK Desa Dolok Maraja dalam menciptakan produk sabun berbahan baku jelantah yang merupakan kebutuhan dalam rumah tangga. Pemateri beserta instruktur dari dosen Prodi Pendidikan Fisika dan Kimia datang ke Desa Dolok Maraja, kemudian memberikan informasi dan pelatihan kepada ibu-ibu PKK tentang pembuatan sabun berbahan baku jelantah. Berdasarkan hasil rata-rata skor nilai dari evaluasi dan pendampingan yang dilakukan oleh tim PKM Unimed, proses pembuatan sabun padat yang diikuti 10 pesert, mampu menguasa imateri dengan kategori Sangat Baik. Untuk pembuatan sabun cair dengan 16 peserta berkategori Baik. Sedangkan untuk pembuatan sabun colek termasuk dalam kategori kurang menguasai karena prosesnya cukup panjang.